Mesa redonda: Diez años de reforma del Derecho del Trabajo (1977-1987) - Calvo Ortega, Rafael; Crespo Valera, Segismundo; Sagardoy Bengoechea, Juan Antonio; Suárez González, Fernando (Revista de Fomento Social, 1988)
.